Homoeologous GSL-ELONG gene replacement for manipulation of aliphatic glucosinolates in Brassica rapa L. by marker assisted selection - Hirani, Arvind H.; Zelmer, Carla D.; McVetty, Peter B.; Daayf, Fouad; Li, Genyi (Frontiers in Plant Science, 2013)
Aliphatic glucosinolates are the predominant sulphur-rich plant secondary metabolites in economically important Brassica crops. Glucosinolates and their hydrolysis products are involved in plant-microbe, plant-insect, plant-animal and plant-human interactions. It is, therefore, important to manipulate glucosinolate profiles and contents in Brassica species. In this study, aliphatic glucosinolates were genetically manipulated through homoeologous recombination in backcross lines followed by marker assisted selection in B. rapa. A resynthesized B. napus line, from a cross between B. rapa and B. oleracea, was backcrossed with Chinese cabbage doubled haploid line, RI16. Marker assisted selection for non-functional gene was performed in each backcross generations. Advanced backcross progenies (BC3F2) were developed to identify homoeologous gene replacement and/or introgression. Reduction in 5C aliphatic glucosinolates (gluconapoleiferin, glucoalyssin and glucobrassicanapin) was observed in BC3F2 progenies of the recurrent parent that carried the GSL-ELONG gene. The GSL-ELONG positive backcross progenies were also screened by the A-genome and BraGSL-ELONG gene specific marker, which linked with 5C aliphatic glucosinolates. The A-genome specific marker was absent in the plants of advanced backcross progenies which showed reduction in 5C aliphatic glucosinolates. The results suggest that the functional allele had been replaced by the non-functional GSL-ELONG allele from B. oleracea. Some advanced backcross progenies (BC3F2) positive for the GSL-ELONG allele and the A-genome specific SCAR marker BraMAM1-1 did not show reduction in 5C aliphatic glucosinolates, suggesting that GSL-ELONG allele is recessive. Replacement of the functional locus in the A genome by non-functional counterpart in the C genome reduced the content of 5C aliphatic glucosinolates in B. rapa seeds with 20 micromoles per gram.